2022
DOI: 10.1029/2021jb023459
|View full text |Cite
|
Sign up to set email alerts
|

Paleosecular Variations During the Last Glacial Period From Tengchong Qinghai Lake, Yunnan Province, China

Abstract: In recent years, the evolution of the magnetic flux lobes in terms of location and intensity has been attributed to paleosecular variation of the geomagnetic field, reflecting outer‐core fluid convection close to the core‐mantle boundary. However, most results were based on observational data for the past 400 years supplemented by sparse archeomagnetic studies with data for approximately 3 kyr. In this paper, we construct a relative paleointensity (RPI) record and an inclination record spanning the past ∼90 ky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 68 publications
(170 reference statements)
0
14
0
Order By: Relevance
“…However, the Bohai Sea RPI stack differs significantly from the low-latitude results of Tengchong Qinghai Lake (98.57°E, 25.13°N, Figure 8c; X. Yang et al, 2022) and core OR1-715-21 (121.29°E, 22.7°N, Figure 8d; Huang et al, 2014), particularly during the intervals of ∼700 to 300 BCE and ∼100 to 500 CE, where the low-latitude (Figures 8c and 8d) records are opposite to the mid-latitude records (Figures 8a and 8b).…”
Section: Late Holocene Paleointensity Variations In East Asiamentioning
confidence: 81%
See 2 more Smart Citations
“…However, the Bohai Sea RPI stack differs significantly from the low-latitude results of Tengchong Qinghai Lake (98.57°E, 25.13°N, Figure 8c; X. Yang et al, 2022) and core OR1-715-21 (121.29°E, 22.7°N, Figure 8d; Huang et al, 2014), particularly during the intervals of ∼700 to 300 BCE and ∼100 to 500 CE, where the low-latitude (Figures 8c and 8d) records are opposite to the mid-latitude records (Figures 8a and 8b).…”
Section: Late Holocene Paleointensity Variations In East Asiamentioning
confidence: 81%
“…Over the past 7,000 years, there have been two or three intense magnetic flux lobes beneath North America, Europe, and Siberia in the Northern Hemisphere (Bloxham et al., 1989; Korte & Holme, 2010). The expansion and intensification of these magnetic flux lobes would influence the behavior of regional magnetic fields (Gallet et al., 2009; X. Yang et al., 2022). Variations in the Bohai Sea RPI may reflect the varying activity of the Siberian surface lobe, which originates from the Siberian flux lobe located on the CMB (Bloxham & Gubbins, 1985; Livermore et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) and X. Zang et al. (2022). A total of 679 and 1,068 discrete sediment samples were taken at ∼2.5 and ∼2 cm stratigraphic intervals from the TCQH4 and TCQH17A cores, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Here we characterized EM variations over the LGP in Southwest China based on environmental magnetism proxies in two long sediment cores (TCQH4 and TCQH17A) from TCQH Lake (Figure S1c in Supporting Information ). Accelerator mass spectrometry (AMS) 14 C ages, combined with relative paleointensity (RPI) data indicated that the two cores contained material deposited continuously since approximately 90 kyr BP (before present, where present = 1950 A.D.; Z. Yang et al., 2022). Combined with the ISM intensity, which was previously reconstructed by the leaf wax hydrogen isotope (δD wax ) record in the TCQH17A core (Zhao et al., 2021), we provide new insights into the terrestrial EM pattern in Southwest China since the LGP.…”
Section: Introductionmentioning
confidence: 99%